Study of islet amyloid polypeptide aggregation and its inhibition mechanisms. - Wei, Lei. (2011)
Islet amyloid polypeptide (IAPP), a 37-amino acid polypeptide hormone of calcitonin family, is co-expressed and co-secreted with insulin in pancreatic islet β cells. Abnormal aggregation of islet amyloid polypeptide (IAPP) into amyloid fibrils is a hallmark of type 2 diabetes. Determining the molecular mechanisms of IAPP aggregation and its inhibition are of paramount importance to understand the pathogenesis of type 2 diabetes and design possible therapeutics. The interactions between IAPP and insulin in the secretory granules are believed to inhibit the aggregation of amyloid fibrils. In this study, presented NMR analysis shows that IAPP, free in solution and in complex with insulin, retains elements of residual secondary structure. NMR chemical shifts and 15N relaxation data indicate that the transiently populated helical structure in residues 11−18 is essential for interactions with insulin. These interactions are mediated by salt bridges between positively charged residues Arg11 or Arg18 of rat IAPP and Glu13 of insulin B chain as well as by hydrophobic interactions flanking the salt bridges. The insulin binding region is composed of the same amino acids in amyloidogenic human IAPP and soluble rat IAPP (with the sole exception of His/Arg-18), implying the same binding mode for both hormones. This His/Arg-18 mutation results in reduced affinity binding of human IAPP to insulin in comparison to rat IAPP as it is detected by surface plasmon resonance biosensor analysis.